Increasing Efficiency Of The Surface Of The Separator Mesh (Texas Journal of Engineering and Technology, 2022)
The mesh surface located in the separator working chamber is fixed and has a circular shape. The holes of the mesh surface are 6 mm in diameter. The suction, mixed with air, enters the working chamber of the cotton separator moving in the tube of the pneumotransport device and falls into the vacuum valve under the influence of its inertia.